TECHNOLOGY IN THE CLASSROOM. - G’aniyeva, Hayriniso (Maktabgacha taʼlim jurnali, 2023)
Technology is becoming an indispensable part of our life and our education system as well. Teachers and students can benefit from technology.This article aims to discover the benefits technology can bring to the classroom, and some of the useful and effective methods that teachers can use in the lessons in order to enhance student motivation and student’s engagement in class.